2020
DOI: 10.13031/trans.13654
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sowing Date, Irrigation, and Nitrogen Management of Summer Maize Using the DSSAT-CERES-Maize Model in the Guanzhong Plain, China

Abstract: HighlightsGood applicability of DSSAT was validated in simulating summer maize yield in the Guanzhong Plain, China.Optimal sowing dates of summer maize were obtained for different climatic years.The optimal irrigation and nitrogen management strategy conserved water and nitrogen. Abstract. Agricultural system models play an important role in simulating crop growth processes and water and fertilizer regulation in arid regions. To solve the current problems of optimizing the sowing date in different climatic yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Optimal fertilization strategies to reduce NO 3 – accumulation in deeper soils while still meeting crop demand should also be considered . In the GP, the N fertilizer application rate varies greatly among farmers, both in croplands and orchards, and their averages significantly exceed the recommended application rate, resulting in a comparatively high N surplus . Inappropriate management practices can also result in excessive N input into the field.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimal fertilization strategies to reduce NO 3 – accumulation in deeper soils while still meeting crop demand should also be considered . In the GP, the N fertilizer application rate varies greatly among farmers, both in croplands and orchards, and their averages significantly exceed the recommended application rate, resulting in a comparatively high N surplus . Inappropriate management practices can also result in excessive N input into the field.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, optimal agricultural water management practices and irrigation schedules to delay historical NO 3 – transport to the aquifer should be considered. Conventional flood irrigation remains the dominant irrigation strategy in the GP, , with the annual average irrigation far exceeding the optimal amount . A study conducted near the GP quantified the main depth of root water uptake of apple trees and indicated that the traditional surface irrigation depth should be reduced to decrease percolation below the root zone, thus increasing water savings .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decision support system for agricultural technology transfer (DSSAT) is one of most widely used crop models for yield prediction (Anar et al, 2019;Dokoohaki et al, 2015;Shen, Xu, et al, 2020;Yakoub et al, 2017), water management (Haberle & Svoboda, 2014;Ben Nouna et al, 2000;Saïdou et al, 2018), and drought reduction (L. Bai et al, 2004;Chen et al, 2013;Igbadun et al, 2008;Shen, Chen, et al, 2020). Crop environment resource synthesis (CERES), a module of DSSAT model, can simulate crop production parameters including growth period and dry matter allocation for crops such as rice (Oryza sativa L.), maize, and wheat (Triticum aestivum L.).…”
Section: Introductionmentioning
confidence: 99%